2023
DOI: 10.3390/su15043661
|View full text |Cite
|
Sign up to set email alerts
|

Physiochemical Properties and Microflora of the Rhizosphere Soil of Tobacco Plants with and without Bacterial Wilt

Abstract: Bacterial wilt is a destructive soilborne disease caused by Ralstonia solanacearum, posing a severe threat to plants in the Solanaceae family. It impacts on tobacco productivity worldwide. This study was conducted to analyze the changes in the soil’s physical and chemical properties, the number of microbes, and the bacterial diversity of the rhizosphere soil before and after the wilt disease. The rhizosphere soil of healthy and diseased tobacco plants was collected from Pucheng, Nanping, Fujian Province, South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Changes in soil chemical conditions affect the structural composition of soil microorganisms to a certain extent (Zheng et al 2023). Previously reported that soil acidi cation can reduce the abundance of carbon-and nitrogen-metabolizing bacteria such as Nitrospirae, Firmicutes, Chlorobi and Zygomycota, which are prone to bacterial wilt (Liu et (Zhang et al 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in soil chemical conditions affect the structural composition of soil microorganisms to a certain extent (Zheng et al 2023). Previously reported that soil acidi cation can reduce the abundance of carbon-and nitrogen-metabolizing bacteria such as Nitrospirae, Firmicutes, Chlorobi and Zygomycota, which are prone to bacterial wilt (Liu et (Zhang et al 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that pH values below 5 or above 8.5 affect the growth and survival of microorganisms [65]. As far as microbiological parameters are concerned, it is important to consider taking appropriate measures to avoid large-scale contamination in the event of drainage by river water, which could affect human health or the evolution of flora [66,67]. In view of the results and the observation of daily household life, and taking into account the technological prowess, education in this area is needed at the household level in Adétikopé with a view to improving wastewater management practices [68].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that pH values below 5 or above 8.5 affect the growth and survival of microorganisms [65]. As far as microbiological parameters are concerned, it is important to consider taking appropriate measures to avoid large-scale contamination in the event of drainage by river water, which could affect human health or the evolution of flora [66,67]. In view of the results and the observation of daily household life, and taking into account the technological prowess, education in this area is needed at the household level in Adétikopé with a view to improving wastewater management practices [68].…”
Section: Discussionmentioning
confidence: 99%